Manual para el impulso de la creación y la aceleración empresarial en la Región Huetar Norte de Costa Rica - Jara-Murillo, Stephanie (Instituto Tecnológico de Costa Rica, 2014)
This project aims at contributing to the successful management of entrepreneurs and business people in the Huetar Norte Region of Costa Rica through proposed steps to be followed to create and accelerate their businesses effectively. This study used a qualitative approach. The study population included 51 member institutions of the Red de Apoyo Pyme Región Huetar Norte. The study techniques used were interviews and document review. The selected sample was 8 institutions. The proposed manual summarizes the main steps since inception of the business idea, the registration of the SME in Ministerio de Economía, Industria y Comercio, the formalization of the business, and the range of options that are available to access financial and non-financial resources offered by member institutions of the Red de Apoyo Pyme Región Huetar Norte.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014
Keywords: Pymes (Pequeña y mediana empresa); Desarrollo empresarial